Kepuasan Pengunjung Pada Fasilitas Wisata di Daya Tarik Wisata Safari Lagoi Bintan Kepulauan Riau - Mita Aprilia Kartini; Youmil Abrian; Nidia Wulansari (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2023)
This research was purposed to describe level of visitor satisfaction at the Safari Lagoi Bintan from indicators: suitability of expectations, revisit intention, and willingness to recommend. The type of this research is descriptive with quantitative data using survey methods. The research was conducted at the Safari Lagoi Bintan, Riau Islands. The population in this research was 9,297 visitors who visited Safari Lagoi Bintan from November 2021-April 2022. The results of this study indicate that: 1) The level of satisfaction about facilities on the suitability of expectations indicators is categorized as satisfied for domestic and foreign visitors, with a score of 4.13 and 4.08; 2) the level of satisfaction on revisit intention indicator is categorized as satisfied for domestic and foreign visitors with a score of 4.15 and 3.96; 3) the level of satisfaction on willingness to recommend indicator is at very satisfied category for domestic visitors, with a score 4.23 and satisfied for foreign visitors with a score of 4.16.